Directly combining a power cycle and refrigeration cycle: Method and case study. (15th November 2022) - Zhao, Dongpeng; Han, Changho; Cho, Wonhee; Zhao, Li; Kim, Yongchan
Abstract: Developing renewable energy and improving the efficiency of energy systems can effectively reduce carbon dioxide (CO2 ) emissions. The combined cycle has attracted attention owing to its high efficiency and variety of products. Although some combined cycles have been proposed in the existing literature, studies focusing on the directly combing method of closed power and refrigeration cycles are rare. This study summarizes the general principles of directly combining power and refrigeration cycles by sharing a thermodynamic process. Four different types of combined cycles were proposed using the Carnot and reversed Carnot cycles. Other combined cycles can evolve from these four combined cycles by considering different practical factors. In addition, an improved combined cycle involving sharing part of the condensation and compression processes between a CO2 power cycle and a vapor compression cycle was proposed. An energy analysis of the improved combined cycle was conducted. There are two operating modes of the improved combined cycle depending on the network output. Within the conditions studied, the maximum coefficient of performance of the improved combined cycle was approximately 0.306 and 0.676 in the cooling and power mode and the cooling mode, respectively. Graphical abstract: Image 1 Highlights: Principles for directly combining power and cooling cycles are summarized. Four ways to directly combine power and refrigeration cycles are introduced. A new combined transcritical power and vapor compression cycle is proposed. The new combined cycle can switch between cooling and cogeneration modes.